Keimanan dan Etos Kerja - Anshori, Afnan (Tasamuh: Jurnal Studi Islam, 2017)
In the teachings of Islam, if someone has expressed faith with said two sentences creed, consequently Islam guarantee her safety and property. Faith in the oneness of God is called monotheism. The tauhid is the subject and the roots of the faith into a buffer all Islamic buildings. Al-Qur’an termed la ailaaha words spoken in a statement illallah creed as Thayyibah sentence. The faith steady obtained as a product of the nature, divine revelation, taste, reason and charity. The five factors that must be turned optimally and simultaneously are how capable, because each interconnected, mutually reinforcing and need each other to produce the faith. Faith as the basis of religious doctrine into who believed unanimously, does not overcome hesitations at all. Faith raises mental attitude, born in word and deed. It is predicated on a belief to worship. Faith is the soul that is in each one of which will be known when spoken in words (creed) and applies to the act (of worship). Meanwhile, work ethic, along with the guidance of Islamic piety. It has been practiced by Muslims in his time ago. When Islam was able to dominate the world of work and affect the human. The entire activity of Muslims cannot be separated from the values of faith. When people work without ethics, without morals and morals, then the human work force imitate animals, down to the level of humility. When people work without the use of reason, then the results of its work will not acquire any progress. Muslims have the Koran and Hadith as the source of all value and guidance in every facet of life, including work